Evaluating the effects of long term exposure to environmental relevant concentrations of real life mixtures of persistent organic pollutants (POPs) in the zebrafish model. - Stavik, Benedicte (2007)
Persistent organic pollutants (POPs) have been widely distributed throughout the world for decades and while the use of some have been phased out, others are still being utilised and their levels are rising in biota. Levels detected in tissue and blood samples have caused for a growing concern for their potential effects on humans and wildlife and many effects studies have been performed. Focus for research has, however, mainly been on high concentrations of single compounds, although it is the realistic levels of real life mixtures of compounds found in the environment that may possess such a threat. In this study, we have investigated the long term effects of environmentally relevant levels of real life mixtures of POPs using the zebrafish as a biomonitor organism. Burbots (Lota lota) from two sites within the same freshwater system in Norway, Lake Mjøsa and Lake Losna, with different history of pollution, were captured and POPs extracted from the liver oil. Zebrafish were exposed indirectly, by exposing their live-food, from start of feeding and until sexual maturation to either the Losna mixture or to one of three dose levels of the Mjøsa mixture. Survival was monitored throughout the experiment while other demographic variables such as growth and sex ratio were evaluated at the time of sexual maturity. Traditional (protein) biomarkers for EROD activity and vitellogenin induction were also measured in addition to organ-specific differences in gene expression pattern using microarray analysis. Exposure resulted in significant lower survival rate and increased growth of the fish, while a small but significant induction was observed in the EROD activity. Analysis of gene expression patterns revealed small changes in mRNA levels though differences were clearly seen. The microarray assay indicated oestrogenic effects of both of the mixtures, in addition to other endocrine disrupting effects related to the steroid- and thyroid hormones. We conclude that long term exposure to real life mixtures of POPs caused ...